MiR-140-5p attenuates chemotherapeutic drug-induced cell death by regulating autophagy through inositol 1, 4, 5-trisphosphate kinase 2 (IP3k2) in human osteosarcoma cells. Issue 5 (14th October 2016) - Wei, Renxiong; Cao, Gang; Deng, Zhouming; Su, Jiajia; Cai, Lin
Abstract : Acquisition of drug-resistant phenotypes is often associated with chemotherapy in osteosarcoma. A number of studies have demonstrated a critical role for autophagy in osteosarcoma development, therapy and drug resistance. However, the molecular mechanisms underlying the autophagy-mediated chemotherapy resistance of osteosarcoma cells remain largely unknown. In the present study, we determined the autophagy and microRNA-140 ( miR-140-5p, miRBase ID: MIMAT0000431) expression induced by chemotherapeutic drugs in osteosarcoma cells. Then we determined the promotory role of miR-140-5p to the chemotherapy-induced autophagy. Our results demonstrated that miR-140-5p expression was highly induced during chemotherapy of osteosarcoma cells, and this was accompanied by up-regulated autophagy. The increased miR-140-5p expression levels up-regulated anticancer drug-induced autophagy in osteosarcoma cells and ameliorated the anticancer drug-induced cell proliferation and viability decrease. Importantly, miR-140-5p regulates this context-specific autophagy through its target, inositol 1, 4, 5-trisphosphate kinase 2 (IP3k2). Therefore, the results of the present study demonstrated that miR-140-5p mediated drug-resistance in osteosarcoma cells by inducing autophagy. The present study provides evidence of miRNA regulation of autophagy through modulation of IP3 signalling. The present study recognized a novel mechanism of chemoresistance in osteosarcoma cancers.